Freedom and necessity in modern Trinitarian theology - Gallaher, Brandon (Oxford theology and religion monographs, 2016)
"Examines the tension between God and the world through a constructive reading of the Trinitarian theologies and Christologies of Sergii Bulgakov (1871-1944), Karl Barth (1886-1968), and Hans Urs von Balthasar (1905-1988). It focuses on what is called "the problematic of divine freedom and necessity" and the response of the writers. "Problematic" refers to God being simultaneously radically free and utterly bound to creation. God did not need to create and redeem the world in Christ. It is a contingent free gift. Yet, on the other side of a dialectic, he also has eternally determined himself to be God as Jesus Christ. He must create and redeem the world to be God as he has so determined. In this way the world is given a certain "free necessity" by him because if there were no world then there would be no Christ. A spectrum of different concepts of freedom and necessity and a theological ideal of a balance between the same are outlined and then used to illumine the writers and to articulate a constructive response to the problematic. Brandon Gallaher shows that the classical Christian understanding of God having a non-necessary relationship to the world and divine freedom being a sheer assertion of God's will must be completely rethought. Gallaher proposes a Trinitarian, Christocentric, and cruciform vision of divine freedom. God is free as eternally self-giving, self-emptying and self-receiving love. The work concludes with a contemporary theology of divine freedom founded on divine election"--